Lost property - Poyiadgi, Andy (Nobrow 17 x 23 series., 2015)
Gerald is a postman, much like many other postmen. One day, having lost a precious and personal item, he visits his local lost and found. Only to find far more than he bargained for, because in this 'self-storage', each and every one of Gerald's lost possessions has been kept and contained. How each item got there, and why they were, was a mystery - but there they all were. What will he do with all his old belongings?